2009
DOI: 10.1007/s11010-009-0058-9
|View full text |Cite
|
Sign up to set email alerts
|

Antilipoperoxidative and membrane stabilizing effect of diosgenin, in experimentally induced myocardial infarction

Abstract: Altered membrane integrity has been suggested as a major factor in the development of cellular injury during myocardial necrosis. The present study was designed to investigate the effect of diosgenin on lysosomal hydrolases, membrane-bound enzymes, and electrolytes during isoproterenol (ISO)-induced myocardial necrosis in rats. Animals were pretreated with DIOS (80 mg/kg) for a period of 35 days. Myocardial infarction was experimentally induced with ISO (85 mg/kg) twice at 24 h interval. Experimental myocardia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(29 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…As diosgenin is the main aglycone of hydrolyzed DNTS, DPTS and DZTS (Tang et al, 2013;Yi et al, 2014b), and in particular, diosgenin have been reported for the anti-myocardial ischemia activity (Jayachandran et al, 2009), we hypothesize that diosgenin, as a metabolite, can be found due to oral administration of these three total saponins; this could constitute part of evidence supporting similarity in efficacy of these three herbs. (2) Are there significant differences in the metabolic profiles and metabolite levels of rat groups administered with saponins from these herbs?…”
Section: Introductionmentioning
confidence: 63%
“…As diosgenin is the main aglycone of hydrolyzed DNTS, DPTS and DZTS (Tang et al, 2013;Yi et al, 2014b), and in particular, diosgenin have been reported for the anti-myocardial ischemia activity (Jayachandran et al, 2009), we hypothesize that diosgenin, as a metabolite, can be found due to oral administration of these three total saponins; this could constitute part of evidence supporting similarity in efficacy of these three herbs. (2) Are there significant differences in the metabolic profiles and metabolite levels of rat groups administered with saponins from these herbs?…”
Section: Introductionmentioning
confidence: 63%
“…The present study showed decreased activities of Na -ATPase which may be attributed to the direct antioxidant activity and antioxidant enzyme-stimulatory effect of vitamin A which thereby protects the -SH group from oxidative damage (33).…”
Section: Discussionmentioning
confidence: 48%
“…Dioscin also increased SOD activity and decreased intracellular ROS and MDA levels (Qin et al 2014). Similarly, cardioprotective effect of diosgenin was observed in isoproterenol-induced myocardial infarction; groups treated with diosgenin had lower levels of CK-MB, lipid peroxidation and lysosomal hydrolysis activity (Jayachandran et al 2009). On the other hand, diosgenin reduced the apoptosis level induced by H 2 O 2 in human vein endothelial cells by increasing SOD, GPX and NOS activity and by reducing free radicals levels (Gong et al 2010).…”
Section: Discussionmentioning
confidence: 88%
“…In traditional medicine diosgenin is used as an anti-hypercholestrolemic, antihypertriacylglycerolemic, anti-diabetic and anti-hyperglycemic agent (Jnarez-Oropeza et al 1987;McAnuff et al 2005;Son et al 2007). Cardioprotective effects of diosgenin were observed in myocardial infarction induced by isoproterenol to its antioxidant and membrane-stabilizing effects (Jayachandran et al 2009). In previous study, we found that this agent reduces the myocardial reperfusion injury through its capacity to inhibit the production of inflammatory cytokines in rat (Ebrahimi et al 2014).…”
Section: Introductionmentioning
confidence: 99%